2018
DOI: 10.3389/fpsyg.2018.02101
|View full text |Cite
|
Sign up to set email alerts
|

Opposition to Inbreeding Between Close Kin Reflects Inclusive Fitness Costs

Abstract: Due to the intense selection pressure against inbreeding, humans are expected to possess psychological adaptations that regulate mate choice and avoid inbreeding. From a gene’s-eye perspective, there is little difference in the evolutionary costs between situations where an individual him/herself is participating in inbreeding and inbreeding among other close relatives. The difference is merely quantitative, as fitness can be compromised via both routes. The question is whether humans are sensitive to the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Since Hamilton's (1964a, b) seminal papers, kin selection has benefitted from more than half a century of intense theoretic development and empirical testing. It has generated powerful, original insights into human behavior, including sibling altruism and attitudes concerning inbreeding among kin that have been upheld by empirical tests (Lieberman et al 2003, Antfolk et al 2018. Should the ideas about GFI that we outline here hold up to direct empirical testing, more refined approaches will be needed to discern the mechanisms and the evolutionary dynamics.…”
Section: Future Opportunities For Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Since Hamilton's (1964a, b) seminal papers, kin selection has benefitted from more than half a century of intense theoretic development and empirical testing. It has generated powerful, original insights into human behavior, including sibling altruism and attitudes concerning inbreeding among kin that have been upheld by empirical tests (Lieberman et al 2003, Antfolk et al 2018. Should the ideas about GFI that we outline here hold up to direct empirical testing, more refined approaches will be needed to discern the mechanisms and the evolutionary dynamics.…”
Section: Future Opportunities For Studymentioning
confidence: 99%
“…Here we describe and model a source of variation in gendered attitudes that generates variability both within and among sexes as a result of what we call 'Gendered Fitness Interests' (GFI). Humans invest time, money and other resources in their kin, and strategic differences in these investments can be driven by relatedness considerations (Alexander 1982, 1987, Betzig and Lombardo 1992, Gaulin et al 1997, Alvard 2003, Jeon and Buss 2007, Lieberman et al 2007, Perry and Daly 2017, Antfolk et al 2018. Our proposal and models aim to provide a method for partitioning these genetic relatedness considerations and applying them to the origins of variation in socio-political attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, there are kin-responsive neurons in the lateral septum ( Clemens et al, 2020 ), which might point to a possible biological basis of kin recognition at least in rodents. Humans use stable psychosocial cues to distinguish different types of kin from non-kin, and the cues used for kin detection depends on the specific dyad ( Lieberman et al, 2007 ; Tal and Lieberman, 2008 ; Antfolk et al, 2018 ; Billingsley et al, 2018 ). One such cue is early co-residence between purported siblings as suggested by Westermarck (i.e., the hypothesis of Westermarck, 1922 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Antfolk, Karlsson, et al (2012) found that biological incest was viewed with more disgust than unrelated incest. Furthermore, disgust ratings for third-party incest are stronger if the raters themselves are related to one of the individuals (Antfolk et al, 2012(Antfolk et al, , 2018.…”
Section: Public Perception Of Csa Subtypesmentioning
confidence: 99%